Girls who rocked the world : heroines from Sacajawea to Sheryl Swoopes - Welden, Amelie, 1975- (Girls know best., 1999)
Tells the stories of thirty-five girls who were younger than twenty years of age when they changed the history of the world through amazing accomplishments.